2011
DOI: 10.1002/jor.21361
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of anterior–posterior rotator cuff force balance improves shoulder function in a rat model of chronic massive tears

Abstract: The rotator cuff musculature imparts dynamic stability to the glenohumeral joint. In particular, the balance between the subscapularis anteriorly and the infraspinatus posteriorly, often referred to as the rotator cuff ''force couple,'' is critical for concavity compression and concentric rotation of the humeral head. Restoration of this anterior-posterior force balance after chronic, massive rotator cuff tears may allow for deltoid compensation, but no in vivo studies have quantitatively demonstrated an impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 28 publications
(59 reference statements)
4
36
0
Order By: Relevance
“…Although previous studies showed that rotator cuff repair in a rat model was sufficient to improve shoulder function using quantitative ambulatory measures, 7,14 this experiment (sharp transection followed by immediate repair) may have not accurately replicated the pathophysiology of rotator cuff tear and rotator cuff repair in clinical settings. Furthermore, in this study we only evaluated the validity of our model over a short time period (21 and 56 days after surgery).…”
Section: Discussionmentioning
confidence: 83%
“…Although previous studies showed that rotator cuff repair in a rat model was sufficient to improve shoulder function using quantitative ambulatory measures, 7,14 this experiment (sharp transection followed by immediate repair) may have not accurately replicated the pathophysiology of rotator cuff tear and rotator cuff repair in clinical settings. Furthermore, in this study we only evaluated the validity of our model over a short time period (21 and 56 days after surgery).…”
Section: Discussionmentioning
confidence: 83%
“…The ratio of the cross-sectional area of the anterior versus posterior rotator cuff muscles also was calculated. This ratio corresponds to the AP force couple of the glenohumeral joint [17] if the shoulder is examined in the same position in the CT gantry before and after surgery [6]. To avoid a learning curve effect, the first 10 images were measured twice.…”
Section: Methodsmentioning
confidence: 99%
“…Restoration of function after tendon damage stemming from injury, overuse, or degenerative disease is largely dependent on the reestablishment of the muscle-tendon-bone connection with minimal scarring between the tendon and its surrounding tissues [16,18]. Current clinical treatment protocols after tendon repair often include NSAIDs, chiefly for their pain-relieving effects, with a secondary indication in their limitation of inflammation [20].…”
Section: Introductionmentioning
confidence: 99%